Shaping Tomorrow’s Citizens: A Comparative Study on Life Skills and Values in Kamrup Metro's Government and Private Schools (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This thesis is an attempt to explore the integration of life skills education and moral values in government and private schools of Kamrup Metropolitan, Assam. It shows how these institutions provide skill-based learning, ethical instruction, and extracurriculars to shape students in personal and social development. The study is both a quantitative and qualitative research approach that identifies disparities in curriculum design, teaching methodologies, and institutional resources. It is characterized by findings indicating that private schools are better able to integrate life skills and value-based education via flexibilities and infrastructures, which government schools find to be lagging in curricula and financial side. And, yet, the gaps would be bridged, via policy-driven reforms and better teacher training. Holistic education which includes academics and character building to make students responsible citizens is the theme of the study. Curriculum restructuring improved pedagogical training, and better collaboration among stakeholders are recommended to make an inclusive and fruitful education system.